Analysis of Growth and Rice Yields (Oryza sativa L.) Conventional, Organic Transitional, and Organic Farming System - Evan Mungara, Didik Indradewa, dan Rohlan Rogomulyo (Vegetalika, 2013)
ABSTRACTA healthy lifestyle has resulted in organic farming system. This study aimed to determine the effect of changes of conventional farming to organic farming system.This research conducted in farmers fields on Tirtosari Village, Sawangan, Magelang regency, Central Java, from December 2011 until April 2012 used menthik wangi susu rice variety. Research compiled in a Completely Randomized Design (CRD) consists of 5 treatments. they were conventional, 3 levels transitional to organic, and organic system. every treatment was repeated 4 times for a total of 20 experimental units. Data were analyzed using analysis of variance (ANOVA) and continued by DMRT test with 95% of significance level.The results showed that changes of conventional farming systems to transitional organic farming at first growing season reduced growth and grain yield. On the next planting season of organic transition had growth and grain yields as high as conventional system and the fully organic cropping system had higher than the conventional system. This result occured due to  the organically grown crops had fewer pests than conventional systems. Grain yield of conventional system was only 3,05 t / ha while the organic system was up to 4,86  t / ha. Keywords: conventional, organic transitional, organic, menthik wangi susu, growth, yield